Assay of Colistin and Colistin Methanesulfonate in Plasma and Urine by Liquid Chromatography-Tandem Mass Spectrometry - Gobin, Patrice (American Society for Microbiology (ASM), 2010)
A rapid high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay was developed for the routine quantification of colistins A and B and their prodrugs, colistin methanesulfonate (CMS) A and CMS B, respectively, in human plasma and urine by using polymyxin B1 as the internal standard (IS). CMS concentrations were determined indirectly by subtracting the colistin concentrations determined in biological samples from the whole colistin concentrations determined after sample treatment with sulfuric acid in order to hydrolyze CMS into colistin. After extraction on a solid-phase extraction column, the colistins were separated on an XBrigde C(18) column with isocratic elution (run time, 3.8 min). The mobile phase was 0.1% (vol/vol) formic acid in acetonitrile-0.1% (vol/vol) formic acid in water (20:80, vol/vol), run at a 0.2-ml/min flow rate. Ions were detected in the turbo-ion-spray-positive and multiple-reaction-monitoring modes. The ions monitored (precursor [M + 2H](2+) to product ions) were m/z 585.5/101.2 for colistin A, m/z 578.5/101.2 for colistin B, and m/z 602.5/241.2 for IS. Prevalidation studies demonstrated the stability of CMS in biological samples and extracts, a key point for the reliable quantification of colistin and CMS. The assay was accurate and reproducible for the quantification of colistins A and B and CMSs A and B in plasma samples over concentration ranges appropriate for pharmacokinetic studies: 0.024 to 6.144, 0.015 to 3.856, 0.029 to 7.492, and 0.010 to 2.508 μg/ml, respectively. In urine samples, the assay was validated over the same concentration ranges for colistins and over concentration ranges of 0.058 to 7.492 μg/ml and 0.020 to 2.508 μg/ml for CMSs A and B, respectively.